Improving Students’ Speaking Ability through Drama For Students Grade XII SMA Santo Thomas Yogyakarta - Betharika Sukendro (Universitas Sarjanawiyata Tamansiswa, 2019)
Between 250-300 words; must focus on: aims of the study, methods, findings, conclusions, and implications. This study discuses the technique to improve students’ ability in speaking English especially for the students of twelfth grade and the students’ respond to the drama technique in teaching speaking. The researcher focuses on the method to improve the speaking ability. The study has two questions as stated in the problem formulation: 1.) How is the use of drama in teaching learning process of speaking at the XII grade of SMA Santo Thomas Yogyakarta? 2.) How were the students’ responses to the application of drama in teaching speaking at the XII grade of SMA Santo Thomas Yogyakarta?This study belonged to classroom action research as a methodology in teaching learning process of speaking. The research involved collaboration and cooperative in learning teaching process of English. Classroom action research occurs through a dynamic and complementary process which was consisting of five essentials moment; reconnaissance, planning, implementation, observation, and reflection. This research consisted of two cycles and each cycle has planning, implementation, observation, and reflection as the research procedure. In each cycle’s researcher using drama technique to deliver the subject of the lesson.The findings of this research showed the improvement in many aspects in teaching learning process of speaking by comparing before and after using drama technique. It indicated that the teaching learning process was successful, both the researcher and the students gained the objectives of teaching and learning process. Based on the result of the research, it showed that drama technique could be applied to improve teaching learning process of speaking for students.